DESIGN OF DROP-OUT BOX SYSTEM FOR PARTICULATE REMOVAL IN OFF-GAS EAF 4 REGARDING HOT METAL BILLET STEEL PLANT REVITALIZATION PROJECT PT KRAKATAU STEEL CILEGON - MEUTIA SARI (NIM: 15313019), THISYA
PT Krakatau Steel (PTKS) Cilegon is one of steelmaking industry in Indonesia. Its process utilizing electric arc furnace (EAF) that emits 1000°C off-gas containing particulate which categorized as toxic hazardous waste. This particulate consists a size of 0.8 microns up to 500 microns, therefore the bag filter in the dedusting system is not sufficient to remove this particulate. After analyzing alternative solution, the gravity settler was chosen as the main component of the drop-out box (DOB) system, functioning as a pre-cleaner. In addition to the gravity settler, the DOB system also consists of a hopper and a dust container. Gravity settler are designed to remove 100% of 80 microns, 200 microns, and 500 microns particulate, as the target removal efficiency is 97.4192%, the total distribution of the particles. In determining the dimensions, width and height are assumed to determine the initial average velocity, then be interposed to adjust the width and height with the availability of the land and the average velocity by design criteria. Having obtained the width, height, and corresponding average velocity, then the length is calculated based on minimum diameter of 100% particulate remove and the width and height dimension already obtained in the beginning. From the calculation, the length, width, and height of settler respectively are 7,753 meter, 8 meter, and 4 meter. Hopper and dust container’s height is 2 meter, with the length and width respectively are 7,753 meter and 8 meter. By this dimension, the settler efficiency reaches 97,44%. Efficiency of the existing bag filter is 97,823%, setting up the total efficiency of particulate removal by gravity settler and bag filter reach 99.94%. By this efficiency, particulate concentration input DOB system of 11,705 mg/m3 and exit the stack as 6,5288 mg/m3.